AMERICAN PHILOSOPHY A PLEA FOR A PEIRCEAN TURN IN ANALYTIC PHILOSOPHY - Nubiola, Jaime (Revista Ética e Filosofia Política, 2018)
Criticisms of analytic philosophy have increased in intensity in the last decade, denouncing specifically its closing in on itself, which results in barrenness and ignorance of real human problems. The thought of C. S. Peirce is proposed as a fruitful way of renewing the analytic tradition and obviating these criticisms. While this paper is largely a reflection on Hilary Putnam’s study of the historical development of analytic philosophy, not only can some of its main roots be traced back to Peirce, but also the recent resurgence of pragmatism can be regarded as a pragmatist renovation of the analytic tradition. Further, Peirce’s thought offers suggestions for tackling some of the most stubborn problems in contemporary philosophy, thereby enabling us to shoulder once more the philosophical responsibility which has been abdicated by much of twentieth-century philosophy. The most accurate understanding of Peirce is to see him as a traditional and systematic philosopher, but one dealing with the modern problems of science truth, and knowledge from a valuable personal experience as a logician and an experimental researcher in the bosom of an interdisciplinary community of scientists and thinkers.